2009
DOI: 10.1002/app.30377
|View full text |Cite
|
Sign up to set email alerts
|

Polymer structure of commercial hydrolyzable tannins by matrix‐assisted laser desorption/ionization‐time‐of‐flight mass spectrometry

Abstract: The structures of six commercial hydrolyzable tannins, chestnut, oak, tara, sumach, chinese gall, and turkey gall tannins have been examined by matrixassisted laser desorption/ionization-time-of-flight (MALDI-TOF) mass spectrometry. Their oligomeric structures and structure distributions have been defined. Degradation products of rather different structure than what previously reported were present. Different galloyl glucose monomers were observed for chestnut and oak tannin extracts and in chinese gall gallot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 15 publications
1
66
0
Order By: Relevance
“…In recent years, MALDI‐TOF‐MS has been widely used to analyze the structure of biological macromolecules and polymers owing to its advantages such as rapidity, accuracy, high sensitivity, high resolution, and wide mass range measurement capability. In comparison with the commonly used method of gel permeation chromatography, MALDI‐TOF‐MS can provide such information as polymers/oligomers molecular weight and their mass distribution range, copolymer composition, and to deduce the most probable reaction mechanism from the species obtained …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, MALDI‐TOF‐MS has been widely used to analyze the structure of biological macromolecules and polymers owing to its advantages such as rapidity, accuracy, high sensitivity, high resolution, and wide mass range measurement capability. In comparison with the commonly used method of gel permeation chromatography, MALDI‐TOF‐MS can provide such information as polymers/oligomers molecular weight and their mass distribution range, copolymer composition, and to deduce the most probable reaction mechanism from the species obtained …”
Section: Resultsmentioning
confidence: 99%
“…In comparison with the commonly used method of gel permeation chromatography, MALDI-TOF-MS can provide such information as polymers/oligomers molecular weight and their mass distribution range, copolymer composition, and to deduce the most probable reaction mechanism from the species obtained. [51][52][53] To further study the molecular weight and oligomers distribution of the GUF resin and to deduce the reaction mechanism of MMU with G, the MALDI-TOF-MS spectra of the GUF resins with MMU/G molar ratio of 1.0 is shown in Figure 8.…”
Section: Maldi-tof-ms Of the Guf Resins With Different Mmu/g Molar Ramentioning
confidence: 99%
“…The hydrolysable tannin content was analysed with the rhodanine method and expressed as gallotannin equivalents (Makkar, ). Matrix‐assisted laser desorption/ionisation time of flight mass spectrometry (MALDI‐TOF MS) was used to characterise the structure of hydrolysable tannin (Pizzi, Pasch, Rode, & Giovando, ), and results showed that the CT contained (DM basis) 78 g/kg digalloyl glucose, 51 g/kg trigalloyl glucose, 164 g/kg pentagalloyl glucose and 707 g/kg oligomers of digalloyl glucose, trigalloyl glucose and pentagalloyl glucose.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrolyzable tannins are complex mixtures of sugar monomers or polymers esterified with polyphenols such as gallic acid and its derivatives and closely related compounds [29][30][31]; typical constituent structures are exemplified in the figure.…”
Section: Tanning With Hydrolyzable Tanninsmentioning
confidence: 99%